Superinsulating BNNS/PVA Composite Aerogels with High Solar Reflectance for Energy-Efficient Buildings - Yang, Jie; Chan, Kit‑Ying; Venkatesan, Harun; Kim, Eunyoung; Adegun, Miracle Hope; Lee, Jeng‑Hun; Shen, Xi; Kim, Jang‐Kyo (Nano-Micro Letters, 2022)
With the mandate of worldwide carbon neutralization, pursuing comfortable living environment while consuming less energy is an enticing and unavoidable choice. Novel composite aerogels with super thermal insulation and high sunlight reflection are developed for energy-efficient buildings. A solvent-assisted freeze-casting strategy is used to produce boron nitride nanosheet/polyvinyl alcohol (BNNS/PVA) composite aerogels with a tailored alignment channel structure. The effects of acetone and BNNS fillers on microstructures and multifunctional properties of aerogels are investigated. The acetone in the PVA suspension enlarges the cell walls to suppress the shrinkage, giving rise to a lower density and a higher porosity, accompanied with much diminished heat conduction throughout the whole product. The addition of BNNS fillers creates whiskers in place of disconnected transverse ligaments between adjacent cell walls, further ameliorating the thermal insulation transverse to the cell wall direction. The resultant BNNS/PVA aerogel delivers an ultralow thermal conductivity of 23.5 mW m−1 K−1 in the transverse direction. The superinsulating aerogel presents both an infrared stealthy capability and a high solar reflectance of 93.8% over the whole sunlight wavelength, far outperforming commercial expanded polystyrene foams with reflective coatings. The anisotropic BNNS/PVA composite aerogel presents great potential for application in energy-saving buildings. Highlights: 1 Highly porous aerogel with longitudinally aligned channels and whisker-like ligaments is constructed by solvent-assisted unidirectional freezing. 2 The thermal insulation and solar reflection capabilities of the composite aerogel reach a state-of-the-art level. 3 The composite aerogel capable of infrared stealth and temperature preservation presents great potential for application in energy-saving buildings.